The determinants of the success of microenterprise: a case study of BRI clients in Medan City, Indonesia / Weni Hawariyuni, Gairuzazmi Mat Ghani and Alias Mat Derus - Hawariyuni, Weni; Mat Ghani, Gairuzazmi; Mat Derus, Alias (Universiti Teknologi MARA Selangor, 2014)
This study focuses on the determinants of the success of microenterprise owners in receiving loan from one of the successful microfinance institutions in the world, namely BRI Unit in Medan city, North Sumatra, Indonesia. This study applies the methodology before and after approach for measuring the success. It utilizes some financial indicators to measure the success of the microenterprises such as income, fixed assets, and household expenditures